Cost Analysis of Endoscopic Carpal Tunnel Release with MAC versus Local Anesthesia - Dondapati, Akhil; Carroll, Thomas J.; Park, Andrew J.; Ketonis, Constantinos (Journal of Wrist Surgery, 2025)
Background The number of annual endoscopic carpal tunnel releases (ECTR) has been increasing due to comparable outcomes with open carpal tunnel release (CTR). Many studies have demonstrated cost-saving measures with open CTR, but similar studies for ECTR are lacking.Purpose The purpose of this study was to analyze differences in the costs associated with ECTR under local anesthesia and monitored anesthesia care (MAC).Materials and Methods We retrospectively compared the surgical costs of 844 patients undergoing isolated ECTR between 2018 and 2024. Patients undergoing isolated ECTR were identified using current procedural terminology code 29848. This included 187 patients undergoing ECTR with MAC and 657 with local anesthesia. The total hospital billed procedure, anesthesia, supply, and postoperative care cost was calculated for each group of patients. Total time spent at the surgical center and insurance type were also recorded. Univariate statistical analysis was completed.Results ECTR under local anesthesia was associated with shorter overall time spent in the surgical center compared to MAC anesthesia (148.12 minutes vs. 224.41 minutes). Total hospital-billed procedure cost was significantly lower in the local anesthesia group ($5,643 vs. $9,073), representing an overall cost reduction of $3,430.15. For the local group, there was also an overall lower cost of supplies ($725 vs. $811), anesthesia cost ($0 vs. $994), medication cost ($10 vs. $69.50), and operating room/recovery time cost ($4,844 vs. $6,822). The insurance type distribution between the two groups was significantly different, with the local group having a higher percentage of private insurance.Conclusion Patients undergoing ECTR with local anesthesia demonstrated overall shorter time spent in the surgical center with reduced total hospital billed procedure, anesthesia, medication/supply, and operating room/recovery room cost. ECTR with local anesthesia was associated with an overall cost reduction of $3,430.15 compared to MAC and local.Level of Evidence Therapeutic III.
Keywords: Carpal tunnel; endoscopic carpal tunnel; anesthesia; local anesthesia